AN EP1DEMOLOGICAL STUDY OF SMOKING AT ABBOTTABAD - Jaleel, Muhammad Asif; Noreen, Rozina; Hameed, Abdul; Hussain, Altaf; Rauf, Shahid; Ali, Liaqat; Tanoli, Taj (Journal of Ayub Medical College Abbottabad, 2001)
Background: Smoking is a type of environmental pollution and is injurious to health. We conducted an epidemiological study of different forms of smoking like cigarette. Hookah (Hubble- Bubble) and cigar in Abbottabad. Methods: 600 randomly selected subjects residing in different localities of Abbottabad were included. A specifically designed questionnaire was filled. Results: Out of the study population 200 (33%) were found to be smoking. Conclusions: A significant proportion of Abbottabad population smokes. This city is supposed to be a relatively less polluted hill station where a lot of people come for vacations.